Rethinking successful aging concepts: Insights from a culturally grounded model among older adults in Odisha, India - Aditya Narayan Das; Smita Mishra Panda; Anjali Dash (Journal of Public Health and Development, 2026)
Despite the widespread use of the biomedical model of successful aging, it overlooks the cultural and lived experiences of older adults in low- and middle-income countries, such as India. Therefore, this cross-sectional study aims to empirically test a culturally grounded model of successful aging in India. Using a multistage stratified sampling with a structured interview schedule, this study used 600 older adults aged 60 years and above from Odisha, India. We used a dichotomous measure of successful aging, which includes 1) being free from disability, 2) having high cognitive function, 3) being engaged in physical activity, 4) experiencing social engagement, and 5) having a positive attitude towards physical health. Descriptive statistics and correlation analysis were carried out to present the initial results. An association between successful aging and explanatory variables was carried out by multivariable logistic regression. One in five older adults fulfilled the requirements for successful aging with rural disadvantage. Being highly educated (AOR: 8.47; 95% CI: 2.89-24.82), having higher wealth (AOR: 4.86; 95% CI: 1.14-20.68), and living with a spouse only (AOR: 8.51; 95% CI: 1.91-37.98) had higher odds of successful aging. Positive psychology towards physical health had a strong positive correlation with successful aging (r = 0.68, p